2011
DOI: 10.1074/jbc.m110.216226
|View full text |Cite|
|
Sign up to set email alerts
|

In TNF-stimulated Cells, RIPK1 Promotes Cell Survival by Stabilizing TRAF2 and cIAP1, which Limits Induction of Non-canonical NF-κB and Activation of Caspase-8

Abstract: RIPK1 is involved in signaling from TNF and TLR family receptors. After receptor ligation, RIPK1 not only modulates activation of both canonical and NIK-dependent NF-B, but also regulates caspase-8 activation and cell death. Although overexpression of RIPK1 can cause caspase-8-dependent cell death, when RIPK1؊/؊ cells are exposed to TNF and low doses of cycloheximide, they die more readily than wild-type cells, indicating RIPK1 has pro-survival as well as pro-apoptotic activities (1, 2). To determine how RIPK1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
50
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 40 publications
7
50
1
Order By: Relevance
“…Of note, at the concentrations used, cell death occurred more rapidly with the TAK1 kinase inhibitor than with the SM. As negative control, we treated the MEFs with TNF in the presence of low concentration of CHX (TNF þ CHX) and, as previously reported, 13 observed that Ripk1 À / À MEFs were not protected but sensitized to this apoptotic trigger (Supplementary Figure S2). Interestingly, we found that inhibiting RIPK1 kinase activity by Nec-1-protected Ripk1 þ / þ MEFs to either TNF þ TAK1i or TNF þ SM as efficiently as the RIPK1 deficiency itself (Figures 1c and d, Supplementary Figures S1A and B).…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…Of note, at the concentrations used, cell death occurred more rapidly with the TAK1 kinase inhibitor than with the SM. As negative control, we treated the MEFs with TNF in the presence of low concentration of CHX (TNF þ CHX) and, as previously reported, 13 observed that Ripk1 À / À MEFs were not protected but sensitized to this apoptotic trigger (Supplementary Figure S2). Interestingly, we found that inhibiting RIPK1 kinase activity by Nec-1-protected Ripk1 þ / þ MEFs to either TNF þ TAK1i or TNF þ SM as efficiently as the RIPK1 deficiency itself (Figures 1c and d, Supplementary Figures S1A and B).…”
Section: Resultsmentioning
confidence: 60%
“…5,11 Under these conditions, TNF-mediated death was shown not to depend on RIPK1. 12,13 cIAP1/2 are required for TNF-induced canonical NF-kB activation. 10,[14][15][16] Consequently, their depletion, obtained either genetically or by the use of Smac Mimetics (SM), also induces a switch to apoptosis.…”
mentioning
confidence: 99%
“…In the absence of Z-VAD (TC), TRAF2 KO MEFs showed stronger TNFα-induced cell death and casapse-8 activation than did WT MEFs (Figures 1b and c), consistent with earlier evidence that TRAF2 suppresses cell-extrinsic apoptotic signaling. 34,40 TRAF2 siRNA knockdown in WT MEFs also enhanced TNFα-induced necroptosis (Figure 1d and Supplementary Figure 1C). Knockdown of RIPK1, RIPK3 or MLKL attenuated TCZ-induced death in TRAF2 KO MEFs, suggesting that TRAF2 regulates necroptosis via the (Figure 2b and Supplementary Figure 2A).…”
Section: Resultsmentioning
confidence: 84%
“…31,33,41,47 TRAF2 inhibits TNFα-induced apoptosis independent of its role in NF-κB activation. 40,48 TRAF2 also suppresses death-receptor-mediated apoptosis by promoting K48-ubiquitination and proteasomal degradation of activated caspase-8. 34 The present findings demonstrate that TRAF2 plays an additional role in curbing necroptotic TNFα signaling by acting both upstream and downstream of the necrosome.…”
Section: Discussionmentioning
confidence: 99%
“…While caspase-8-and FADD-deficient mice die at embryonic stage 10.5, they are rescued, at least in part, by co-deletion of RIPK1 and RIPK3. 52,83,84 Therefore, caspase-8 appears to be required to suppress caspase-independent necroptosis mediated by RIPK3.…”
Section: Ciaps In Tnf-r1 Signallingmentioning
confidence: 99%